2011
DOI: 10.1007/s00011-011-0362-1
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids exhibit anti-inflammatory effects in human monocytic leukemia cell line, THP-1 cells

Abstract: Our results suggest that cysteine and histidine exhibit anti-inflammatory effects in THP-1 cells, and may be responsible for the efficacy of treatment in inflammatory bowel diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…We have studied NF‐κB activation previously in various cell types, including HCAECs in vitro [18–20]. We have also reported that histidine and cysteine exhibit anti‐inflammatory effects on THP‐1 cells, a human acute monocytic leukaemia cell line [21]. In this study, we showed that glycine, histidine and cysteine, but not alanine, inhibited NF‐κB activation and IκBα degradation by stimulation with TNF‐α.…”
Section: Discussionmentioning
confidence: 56%
“…We have studied NF‐κB activation previously in various cell types, including HCAECs in vitro [18–20]. We have also reported that histidine and cysteine exhibit anti‐inflammatory effects on THP‐1 cells, a human acute monocytic leukaemia cell line [21]. In this study, we showed that glycine, histidine and cysteine, but not alanine, inhibited NF‐κB activation and IκBα degradation by stimulation with TNF‐α.…”
Section: Discussionmentioning
confidence: 56%
“…In vitro , histidine inhibited lipopolysaccharide-induced tumor necrosis factor-alpha production by suppression of nuclear factor (NF)-κB activation in mouse peritoneal macrophages and human monocytes [ 23 ]. Hasegawa et al also reported the inhibitory effects of histidine on the induction of NF-κB activation in THP-1 cells, a human monocytic leukemia cell line, and peripheral blood mononuclear cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Histidine supplementation can suppress oxidative stress- and TNF-α-induced IL-8 secretion in intestinal epithelial cells [ 126 ]. Hasegawa et al [ 127 ] reported that histidine exhibited anti-inflammatory effects in THP-1 human monocytic leukemia cells, and speculated that histidine may also have therapeutic efficacy in IBD. Consistent with this, dietary histidine ameliorated colitis in an IL-10-deficient (IL-10 −/− ) cell transfer model of Crohn’s disease, by regulation of NF-κB activation, and subsequent inhibition of proinflammatory cytokine production by macrophages [ 71 ].…”
Section: Potential Roles Of Amino Acids In Ibdmentioning
confidence: 99%